(untitled) (Anclajes, 2025)
The texts that constitute the corpus of feminine mystical writing maintain a fluid and constant conversation or exchange with the divine that each writer understands in her own way. Although there is no written record of the dialogue that the Costa Rican poet Eunice Odio had with God, it is possible to track and assemble the traces of those conversations through her correspondence with the Venezuelan editor Juan Liscano, where the experience of the supernatural and the divine runs through the personal and professional contents of the texts. Odio’s letters, which belong to a tradition that dates to the Beguine writers of the 13th century, insist that the language and aesthetics of Judeo-Christian mysticism have worked and still serve as strategies for some Latin American poets searching for new ways to discuss themselves, their bodies and their worlds.